Nationalization in U.S. Senate and Gubernatorial Elections. Issue 5 (September 2019) - Sievert, Joel; McKee, Seth C.
Since the 1970s, American politics has taken an impressive turn away from political dealignment and moved toward a more responsible party system. As a result, elections have become more nationalized, a process by which presidential and national politics exert greater influence over down-ballot contests. We evaluate nationalization in electoral contests for two high-profile offices—U.S. Senate and governor—that encompass the same constituencies but constitute markedly different job descriptions and mandated responsibilities. Our analysis utilizes both macro- and micro-level data (election returns and surveys, respectively) to assess patterns of nationalization in these elections. Although it is perhaps not surprising that the linkage between presidential and senatorial contests has tightened, it appears national political forces now also exert greater influence over gubernatorial contests. Nonetheless, we do find regional variation in the nationalization of senatorial and gubernatorial politics, which is more evident in the latter office.